Genome aberrations in canine mammary carcinomas and their detection in cell-free plasma DNA. - Julia Beck; Silvia Hennecke; Kirsten Bornemann-Kolatzki; Howard B Urnovitz; Stephan Neumann; Philipp Ströbel; Franz-Josef Kaup; Bertram Brenig; Ekkehard Schütz (PLoS ONE, 2013)
Mammary tumors are the most frequent cancers in female dogs exhibiting a variety of histopathological differences. There is lack of knowledge about the genomes of these common dog tumors. Five tumors of three different histological subtypes were evaluated. Massive parallel sequencing (MPS) was performed in comparison to the respective somatic genome of each animal. Copy number and structural aberrations were validated using droplet digital PCR (ddPCR). Using mate-pair sequencing chromosomal aneuploidies were found in two tumors, frequent smaller deletions were found in one, inter-chromosomal fusions in one other, whereas one tumor was almost normal. These aberrations affect several known cancer associated genes such as cMYC, and KIT. One common deletion of the proximal end of CFA27, harboring the tumor suppressor gene PFDN5 was detected in four tumors. Using ddPCR, this deletion was validated and detected in 50% of tumors (N = 20). Breakpoint specific dPCRs were established for four tumors and tumor specific cell-free DNA (cfDNA) was detected in the plasma. In one animal tumor-specific cfDNA was found >1 year after surgery, attributable to a lung metastasis. Paired-end sequencing proved that copy-number imbalances of the tumor are reflected by the cfDNA. This report on chromosomal instability of canine mammary cancers reveals similarities to human breast cancers as well as special canine alterations. This animal model provides a framework for using MPS for screening for individual cancer biomarkers with cost effective confirmation and monitoring using ddPCR. The possibility exists that ddPCR can be expanded to screening for common cancer related variants.